Islamization of sociology in theory and practice - Md. Noon, Hazizan (2011)
Modern sociology is basically the product of the Western tradition despite some direct and indirect contributions of other traditions including the Islamic one to the evolution of such an organized body of sociological knowledge. Modern Western tradition, culture and civilization are known to be secular in essence and outlook. Being secular in many ways, modern sociology is found to be incapacitated to fully and accurately comprehend and explain the nature of the non-Western societies especially the Muslim societies. While many aspects and elements of the Western oriented sociology are undoubtedly acceptable to the contemporary Muslims, legitimate questions may be raised as to the acceptability of the other aspects/elements as far as Islamic religious teachings and principles are concerned. It is in this context that this presentation finds its justification i.e. to critically examine and disclose the aspects and elements of such incompatibility of modern sociology with Islam. In essence, the presentation reflects critical attitude of contemporary Muslim academics towards and response to this modern sociology.